The queen's coronation : a novel - Ryan, Jennifer (Jennifer L.) (Ballantine Books, 2026)
London, 1953. Buckingham Palace and the employees who are vital to the smooth running of the monarch find themselves in bedlam as thecoronation approaches. Caroline Brimstone, assistant dresser to thequeen, watches as the queen finds the strength to rule. Lucy Jones is a young, idealistic, eager junior wardrobe assistant who yearns to become a famous singer. Miranda Miller is an American temporary secretary. As all three women discover, just because a woman will soonbe sitting atop the throne, it doesn't mean the society will changeover night. If they want to make a place for themselves in the world, they will have to carve it out together.